Successive prepositions in Croatian as translational equivalents of Turkish semi-postpositions : ungrammaticality or necessitiy? - Kerovec, Barbara (Array, 2011)
The paper examines the way of expressing some aspects of dynamic spatial relations by prepositions in Croatian and semi-postpositions in Turkish. Semi-postpositions, the meanings of which correspond mostly to the meanings of prepositions in Croatian, are nouns by origin. Their inflectional variability enables easy, economical, and precise encoding of source (ablative) and goal (dative) point, as well as stativity (locative). In Croatian, by contrast, these three different relations can sometimes be expressed by same grammatical means, which can lead to imprecision of the expression (e.g., the sentence Pojavio se iza kuće. “He appeared (from) behind the house” can be understood only from the context, i.e. from speaker’s perspective). Nevertheless, in Croatian, particularly in informal language, we can notice the use of successive prepositions (source point: od iza kuće “from behind the house”, goal point: do iza kuće “(to) behind the house”). It is a matter of discussion whether these constructions arise from a need for achieving precision by less lexical means, or whether they are simply ungrammatical. It is interesting that the grammatical structure of double prepositional constructions in Croatian is similar to Turkish semi-postpositional constructions in spite of the typological differences between the two languages. Such similarities can be explained by similarities in conceptualization of space.